A retrospective study of analysis of various factors affecting the outcome of sepsis in neonates admitted to a tertiary care neonatal intensive care unit - Chinnusamy, Krishnakumar; K., Devimeenakshi (International Journal of Research in Medical Sciences, 2016)
Background: Sepsis is an important contributor to neonatal mortality and morbidity. Our aim was to study the various factors determining the outcome in neonatal sepsis in tertiary care hospital. Study was conducted in NICU of Government Stanley medical college, Chennai, India. Methods: Designed as retrospective study, based on case records of babies admitted between July to December 2015. Out of the 320 cases admitted during the study period, 120 babies with clinical features suggestive of neonatal sepsis. Risk factors were analyzed for their association with the outcome. Results were statistically analyzed. Results: Among the parameters studied it was observed that birth weight of the baby (p<0.001 ), maturity of the baby (p = 0.002) and laboratory parameters like abnormal leukocyte count ( p<0.001 ) and abnormal platelet count (p<0.001) were significantly associated with poor outcome. These variables retained their significance when subjected to multiple logistic regression analysis. Conclusions: In our study, we found low birth weight, prematurity, abnormal leukocyte counts and thrombocytopenia on admission were found to be associated with poor outcome.